PEMANFAATAN LIMBAH PADAT PT. AMBICO SEBAGAI MEDIA TANAM TERHADAP LAJU PERTUMBUHAN BIBIT PORANG - Yayok Suryo Purnomo; Muhammad Fadillah (EnviroUS, 2022)
PT. Ambico is a company engaged in the food industry with the main raw material from porang tubers. Of course, this will have a negative impact if the high production increase is not accompanied by the utilization of the resulting sludge. Therefore, the use of mud and soil from washing porang tubers really needs to be reused as a mixture of planting media for the growth rate of porang seedlings. The research was conducted by mixing the composition of the growing media from the nursery process. During the process, measurements of porang height, porang diameter and nutritional analysis were carried out at the end of the study (10th week). The parameters tested consisted of pH, N-Total, phosphorus, potassium, Corganic, and C/N ratio. This study aims to determine the optimal composition between the ratio of mud and soil from tuber washing (½:1, 1:1, 1:1 and 2:1) and variations in watering volume (150 ml, 300 ml). , and 600ml). on the growth rate of porang seedlings until the 10th week. The results showed that the S1-P3 reactor experienced the best growth in height and diameter of porang among the compositions of mud and other tuber washing soils. While in control, the K3-P3 reactor experienced the best growth process in terms of height, diameter and nutrient content.